HUBUNGAN ANTARA KARAKTERISTIK PRAMUWISATA DENGAN TINGKAT PENGETAHUAN BANTUAN HIDUP DASAR (BHD) DI BALI - Erviani, Novita Ayu; Juniartha, I Gusti Ngurah; Saputra, I Kadek (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023, 2024)
Tour guides have the duty and responsibility to ensure the safety of tourists, including in the field of health. The frequent occurrence of emergency cases among tourists necessitates tour guides to possess Basic Life Support (BLS) skills. Tour guides can act as lay rescuers in administering CPR for handling emergency cases involving tourists. The aim of this research is to understand the relationship between the characteristics of tour guides and their level of knowledge of Basic Life Support (BLS) in Bali. The research design used is cross-sectional, with 100 respondents selected through purposive sampling technique. Data were collected in April 2022 online using Google Form. The instruments used included a demographic data questionnaire and an anonymous questionnaire regarding the level of BLS knowledge. Spearman's rank statistical test was used in this study. The research results show that the majority have good knowledge (72%). There is a significant relationship between educational level (p<0,0022; r = -0,003) and length of service (p?0,014; r = 0,245) with the level of BLS knowledge among tour guides in Bali, while age, training history, and emergency handling history do not have a significant relationship with the level of BLS knowledge (p>0,05). This indicates a significant relationship between educational level and length of service and the level of BLS knowledge among tour guides in Bali.